(untitled) - Reeder, Carolyn (New York, 1989)
At the end of the Civil War, twelve-year-old Will, having lost all his immediate family, reluctantly leaves his city home to live in the Virginia countryside with his aunt and the uncle he considers a "traitor" because he refused to take part in the war.
"An Avon Camelot book."
Keywords: Orphans; Fiction; Fiction; Conscientious objectors; Fiction; Uncles; Fiction; United States; History; Civil War, 1861-1865; Virginia